2017
DOI: 10.3390/foods6080068
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants in Food: The Significance of Characterisation, Identification, Chemical and Biological Assays in Determining the Role of Antioxidants in Food

Abstract: There is a vast research literature on the antioxidant activity in food. [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Parry et al (2005) evaluated the amount of total phenolic content for cold pressed berry seed oils and the values were found to be 1.73-2.0 mg GAE/g sample (34). To further confirm the antioxidant properties of cold pressed seed oils, ABTS + radical scavenging activity, which is one of the most commonly used methods, was evaluated (35). Different antioxidant activity methods were developed due to the complexity of the oxidation processes, such as DPPH, ABTS radical scavenging activity, oxygen radical absorbance capacity (ORAC), cupric ion reducing antioxidant capacity (CUPRAC) (36,37) etc.…”
Section: Resultsmentioning
confidence: 99%
“…Parry et al (2005) evaluated the amount of total phenolic content for cold pressed berry seed oils and the values were found to be 1.73-2.0 mg GAE/g sample (34). To further confirm the antioxidant properties of cold pressed seed oils, ABTS + radical scavenging activity, which is one of the most commonly used methods, was evaluated (35). Different antioxidant activity methods were developed due to the complexity of the oxidation processes, such as DPPH, ABTS radical scavenging activity, oxygen radical absorbance capacity (ORAC), cupric ion reducing antioxidant capacity (CUPRAC) (36,37) etc.…”
Section: Resultsmentioning
confidence: 99%
“…Bulgarian and Italian gerger studied for the total phenolic content, and the antioxidant potential of ethanol extract suggested a higher antioxidant capacity in Bulgarian gerger than the Italian variety [24]. The method of extraction of food antioxidants affects the nature of compounds isolated, and the quality of the total antioxidant activity [42]. Compounds reported in the soxhlet aided methanol extract of gerger leaves were absent in the gerger leaf decoction reported in this study.…”
Section: Journal Of Food and Nutrition Researchmentioning
confidence: 49%
“…Based in these findings, Myrtaceae fruit peels may show potential antioxidant capacity and may be considered a valuable source of natural antioxidants, preventing the harmful effect of free radicals. Free radicals and reactive oxygen species (ROS) have been considered to contribute to the progress of aging and illness by causing oxidative stress [ 45 , 46 ]. Aimed at improving health, the consumption of these natural sources of substances can be vitally important to the human body.…”
Section: Resultsmentioning
confidence: 99%
“…Few studies report the influence of Myrtaceae fruits on the antiproliferative effects on cancer cells. It has been reported that several flavonoid compounds from M. cauliflora presented antiproliferative activities against HT-29 (IC 50 = 65 μM) and HCT116 (IC 50 = 30 μM) colon cell lines [ 45 ]. Also, there are some findings concerning S. cumini extracts that reported the inhibition on the colon cancer line (HCT116).…”
Section: Resultsmentioning
confidence: 99%